Association of dietary fiber intake with all-cause and cardiovascular mortality in U.S. adults with metabolic syndrome: NHANES 1999–2018 - Guo, Yafei; Li, Meiling; Huang, Yueqin (Frontiers in Nutrition, 2025)
BackgroundLow dietary fiber intake is common in the US, despite its health benefits. Individuals with metabolic syndrome (MetS), at high cardiovascular risk, may benefit significantly from higher fiber, but its link to mortality in this group is unclear.MethodsWe analyzed prospective data from 10,962 U.S. adults with MetS (NHANES 1999–2018, mean age 58.1). Baseline fiber intake (g/day) was assessed via 24-h recalls. MetS was defined by ATP III criteria. Mortality (all-cause, CVD-specific) was tracked via the National Death Index (median follow-up 102 months). Cox models estimated hazard ratios (HRs) for mortality associated with fiber intake, adjusted for demographics, socioeconomic status, lifestyle, and comorbidities.ResultsOver follow-up, 2,617 deaths occurred (887 CVD-specific). Higher fiber intake was associated with significantly lower mortality. Our analysis suggested a potential threshold effect near 21.7 g/day of fiber intake. Below this, each additional 5 g fiber reduced all-cause mortality risk by 7% (HR = 0.93, 95% CI: 0.91–0.96, p < 0.0001). Comparing highest to lowest tertile intake, adjusted HRs were 0.80 (95% CI 0.72–0.89, p < 0.0001) for all-cause and 0.61 (0.51–0.73, p < 0.0001) for CVD mortality. Results were robust in sensitivity analyses.ConclusionIn U.S. adults with MetS, higher dietary fiber intake was associated with significantly lower all-cause and CVD mortality. Benefits were most pronounced at lower intakes, plateauing around 22 g/day, suggesting achieving moderate fiber intake near recommendations offers substantial survival benefits in this high-risk group.